Analisis Faktor Risiko Kejadian HIV/AIDS Berbasis Perilaku Manusia Di Kabupaten Madiun Tahun 2018 - Puri Ratna Kartini (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: HIV / AIDS is a behavior-based disease. The HIV epidemic is a serious problem and challenge to public health in the world both in developed and developing countries such as Indonesia. In Asia, the factors driving the HIV / AIDS epidemic are three high-risk behaviors, namely unprotected commercial sex, sharing syringes in drug users and sex between unprotected men. This study is an observational-analytic study that aims to analyze the influence of human behavior factors included in the practice of free sex, alcohol consumption practices, drug use practices, attitudes and practices of weak religious teachings against the incidence of HIV / AIDS in Madiun Regency.Methods: The research design used was case control, with a purposive sampling technique. Data was taken through interviews to respondents using questionnaires and analyzed using logistic regression tests. This research was conducted in the working area of the Madiun District AIDS Eradication Commission (KPAD) for 6 months, starting from January to June 2018. The case group in this study were 20 HIV-AIDS sufferers selected and the control group was family / neighboring of the HIV / AIDS sufferers who does not suffer from HIV / AIDS as many as 20 people.Result: The results of this study show that the practice of injecting drug use (p> 0.005 which is 1,000) and alcoholic consumption practices (p> 0.005 which is 0.355) is not a risk factor for HIV / AIDS in Madiun Regency. Whereas the risky sex practices and weak religious teaching practices are the risk factors for HIV / AIDS in Madiun Regency which value of p is 0.017 and 0.021.Conclusion : Thus there is a need for counseling efforts about safe sex and to increase faith and piety in order to reduce the risk of transmission of HIV / AIDS in Madiun regency.